Stimuli‐Responsive Ruthenium‐Containing Polymers. Issue 22 (9th August 2018) - Zhou, Hongwei; Chen, Mingsen; Liu, Yuanli; Wu, Si
Abstract: Ruthenium‐containing polymers (RCPs) are a type of functional metallopolymer. Stimuli‐responsive RCPs in which the responsive behaviors derive from the structure variation of Ru complexes are reviewed in this Feature Article, with particular focus on redox responsive RCPs and photoresponsive RCPs. On the basis of the recent progress, the response principle, syntheses, structures, properties, applications, and remaining challenges of such stimuli‐responsive RCPs are discussed. Abstract : Combining ruthenium complexes and polymers results in functional polymers with unique structures and excellent properties. Stimuli‐responsive ruthenium‐containing polymers (RCPs) in which the stimuli‐responsive behaviors derive from the structure variation of ruthenium complexes are reviewed here, focusing on redox responsive RCPs and photoresponsive RCPs.